2010
DOI: 10.4331/wjbc.v1.i10.307
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cancer cell migration and invasion by sphingosine-1-phosphate

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid that has been implicated in regulation of a number of cancer cell malignant behaviors, including cell proliferation, survival, chemotherapeutic resistance and angiogenesis. However, the effects of S1P on cancer cell migration, invasion and metastasis, are perhaps its most complex, due to the fact that, depending upon the S1P receptors that mediate its responses and the crosstalk with other signaling pathways, S1P can either positively or negatively regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Research has shown that the alterations of various oncogenes, tumor suppressor genes, metastasis suppressor genes, and growth factors and their receptors are associated with tumor metastasis [21][22][23]. The fact that Stat3 is activated by numerous cytokines, growth factors, and oncogenic proteins suggests that Stat3 signaling may be one of the common pathways involved in regulating cancer metastasis [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the alterations of various oncogenes, tumor suppressor genes, metastasis suppressor genes, and growth factors and their receptors are associated with tumor metastasis [21][22][23]. The fact that Stat3 is activated by numerous cytokines, growth factors, and oncogenic proteins suggests that Stat3 signaling may be one of the common pathways involved in regulating cancer metastasis [4,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a complex process and the major cause of death in most cancer patients [21][22][23]. Understanding its molecular mechanisms will explore the future directions for more effective biological treatment for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of S1P in both of these processes was recently reviewed [103], and thus, we will only briefly summarize the major findings. The S1P-mediated effect on migration is determined in part by the relative predominance of expressed S1PRs.…”
Section: S1p Migration Invasion and Metastasismentioning
confidence: 99%
“…The diverse physiological processes specifically regulated by the extracellular S1P in a given cell type therefore depend on the repertoire of expressed S1PRs, which couple to various G-proteins and activate numerous signaling pathways. More complete reviews of the downstream signaling of each receptor were published [102][103][104][105]. S1PR1, formerly known as EDG1, was the first identified S1P receptor [89].…”
Section: Extracellular S1pmentioning
confidence: 99%
“…[102] In addition, these effects of S1P are mediated via receptor-dependent pathways that activate different receptors and attribute to diverse effects in various cell lines as we explain later. Hence, S1P1, S1P3, and S1P5 activate cell migration [ Figure 1] through Rac and PLC signaling, despite the fact that S1P2 plays an antimigration effect by Rho signaling.…”
Section: S1p In Tumor Invasion Migration and Metastasismentioning
confidence: 98%